Dynamics of wellbeing co-creation: a psychological ownership perspective. (2nd July 2020) - Chen, Tom; Dodds, Sarah; Finsterwalder, Jörg; Witell, Lars; Cheung, Lilliemay; Falter, Mareike; Garry, Tony; Snyder, Hannah; McColl-Kennedy, Janet R.
Abstract : Purpose: People are responsible for their wellbeing, yet whether they take ownership of their own or even others' wellbeing might vary from actor to actor. Such psychological ownership (PO) influences the dynamics of how wellbeing is co-created, particularly amongst actors, and ultimately determines actors' subjective wellbeing. The paper's research objective pertains to explicating the concept of the co-creation of wellbeing and conceptualizing the dynamics inherent to the co-creation of wellbeing with consideration of the influences of all involved actors from a PO perspective. Design/methodology/approach: To provide a new conceptualization and framework for the dynamics of wellbeing co-creation, this research synthesizes wellbeing, PO and value co-creation literature. Four healthcare cases serve to illustrate the effects of engaged actors' PO on the co-creation of wellbeing. Findings: The derived conceptual framework of dynamic co-creation of wellbeing suggests four main propositions: (1) the focal actor's wellbeing state is the intangible target of the focal actor's and other engaged actors' PO, transformed throughout the process of wellbeing co-creation, (2) PO over the focal actor's wellbeing state is subject to the three interrelated routes of exercising control, investing in the target, and intimately knowing the target, which determine the instigation of wellbeing co-creation, (3) the level of PO over the focal actor's wellbeing state can vary, influence and be influenced by the extent of wellbeing co-creation, (4) the co-creation of wellbeing, evoked by PO, is founded on resource integration, which influences the resources–challenges equilibrium of focal actor and of all other engaged actors, affecting individual subjective wellbeing. Originality/value: This article provides a novel conceptual framework that can shed new light on the co-creation of wellbeing in service research. Through the introduction of PO the transformation of lives and wellbeing can be better understood.